Akuntabilitas dan Transparansi Keuangan Madrasah dalam Perspektif Manajemen Keuangan Modern dan Prinsip Syariah - Kholis Al Arifuttaqi; Mambaul Ngadhimah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzes the integrative model of financial accountability and transparency in a pesantren-based educational institution by examining the synthesis between Islamic principles and modern financial management. Employing a qualitative case study design at MA Miftahussalam Slahung Ponorogo, data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that financial accountability practices in the madrasa extend beyond compliance-based accountability commonly found in general educational institutions and evolve into value-based accountability rooted in the principles of amanah (trustworthiness), ‘adl (justice), shura (deliberation), and mas’uliyyah (transcendental responsibility). While modern financial management instruments such as participatory budgeting, systematic bookkeeping, and internal auditing are adopted, their implementation is infused with spiritual consciousness, forming a pattern of double accountability managerial accountability to stakeholders and spiritual accountability to God. However, the study also reveals a structural gap between strong moral capital and limited technical capital, particularly in digital reporting systems and human resource capacity. These findings demonstrate that spirituality does not substitute professionalism; rather, both dimensions must be structurally and substantively integrated to produce a governance model that is responsive to contemporary public accountability demands while remaining consistent with Islamic ethical foundations.